Peran Badan Penanggulangan Bencana Daerah dalam Pencegahan Bencana Banjir di Kabupaten Jombang - Tukiman; Bayu Rafligo Diazmuda (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Jombang Regency is one of the regencies in East Java that experiences flooding every year. BPBD as a stakeholder responsible for disaster management efforts has taken a number of steps/efforts to reduce the impact of floods. This research aims to analyse and describe the problem of the role of the Regional Disaster Management Agency in flood disaster prevention in Jombang Regency. Descriptive qualitative research method was used in this research. Primary data sources and secondary data were used in this research. Data collection techniques through documentation, interviews and observation. This study uses the theory of the disaster management cycle according to (Khambali, 2017) which focuses on the pre-disaster stage which has 4 indicators including prevention, disaster mitigation, preparedness, and early warning. The results showed that BPBD Jombang Regency has played a role in preventing flood disasters in Jombang Regency. This is evidenced by establishing a Pusdalops, installing disaster signs, forming Disaster Resilient Villages, providing disaster counseling, coordinating with Regional Apparatus Organizations (OPD) and related parties in flood disaster prevention, preparing evacuation sites, socializing regulations/guidelines on disaster management, and providing good early warning. However, in the contingency plan indicator, it was found that BPBD has not yet developed a contingency plan because it is still in the process of being developed.